Silencing and Silence: Language and Specialized Listening in a Long-Term Institution for the Elderly (Global Journal of Human-Social Science, 2020)
This article presents the result of research developed with the language of elderly residents at the Long Term Care Facility for the Elderly -ILPI, in Vitória da Conquista, Bahia, Brazil. In response to the initial questions as to whether institutionalization affects the language of the elderly, whether the resignification of verbal by non-verbal speech occurs, and whether silence, as language is part of an alternative system of possible meaning for the elderly, it was perceived that language in institutionalized long-lived individuals it reveals that in response to diversified processes of silencing, they have instituted silence as a possibility of reframing, and structuring of meaning. We collected data through the filming and recording of the elderly in enunciative-discursive situations, considering the uniqueness of each subject's history and their respective crossings as well as the condition of production of the narratives based on the concept of data-finding by Maria Hadler Coudry (1), aligned with notions relevant to Linguistics in the theoretical-methodological perspective of Discursive Neurolinguistics.
Keywords: language; silence; old man; long-term institution